Two-dimensional nanomaterials for improved photoelectrochemical water splitting - Singh B.; Indra A. (My University, 2025)
A huge progress has been made in the development of two-dimensional (2D) nanomaterials due to their modulated structural and electronic properties. Generally, nanostructured semiconductor photoelectrodes with 2D morphology having strong absorption in visible light, suitable bandgap and band energy levels, fast charge transport, and high density of active sites have been combined with various nanomaterials and employed for the photoelectrochemical water splitting. These materials have shown excellent catalytic performance in photoelectrochemical water splitting. In this respect, the designing of 2D semiconductor(s) is crucial for photoelectrochemical water splitting. 2D nanomaterials such as metal oxides, metal dichalcogenides, metal nitrides, graphitic carbon nitride (g-C3N4), and other carbon-based conductive materials have been explored for photoelectrochemical water splitting. This chapter focuses on the importance of designing 2D nanomaterials, strategies to tune the catalytic performance, and the state-of-the-art 2D nanomaterials employed for photoelectrochemical water splitting. © 2024 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.